Does Mode of Administration Matter? Comparison of Online and Face-To-Face Administration of a Time Trade-Off Task - Norman, Richard; King, M.; Clarke, D.; Viney, R.; Cronin, P.; Street, D. (Springer, 2010)
Purpose. Developments in electronic data collection methods have allowed researchers to generate larger datasets at lower costs, but relatively little is known about the comparative performance of the new methods. This paper considers the comparability of two modes of administration (face-to-face and remote electronic) for the time trade-off.Method. Data were collected from a convenience sample of adults (n = 135) randomised to either a face-to-face time trade-off or a remote electronic tool. Patterns of responses were considered. For each sample, standard regression analysis was undertaken to generate a valuation set, which were then contrasted.Results. The pattern of responses differed by mode of administration, with the electronic tool yielding larger standard deviations and higher proportions of responses at -1, 0 and 1. The impact of this on the regression was difficult to disentangle from the high variability around individual scores of states, which is a common feature of responses to time trade-off tasks. Under the scoring algorithms generated by mode of administration, the difference between scores exceeded 0.1 for 100 of the 243 EQ-5D health states.Conclusions. This comparison demonstrates that variability arising from mode of administration needs to be considered in developing health state valuations. While electronic administration has considerable cost advantages, particular attention to the design of the task is required. This has wider implications, as all modes of administration may have mode-specific impacts on the distribution of valuation responses.